Neutrophil-to-Lymphocyte Ratio and Platelet-to-Lymphocyte Ratio as Potential Predictors of Prognosis in Acute Ischemic Stroke - Chen, Cuiping; Gu, Lei; Chen, Luyun; Hu, Wangwang; Feng, Xiaowen; Qiu, Fengzhen; Fan, Zijian; Chen, Qitao; Qiu, Jiayou; Shao, Bei (Frontiers in Neurology, 2021)
Objective: Neutrophil-to-lymphocyte ratio (NLR) and platelet-to-lymphocyte ratio (PLR) have been emerging as the novel inflammatory biomarkers for determining the prognosis of various diseases. This study aimed to investigate the individual and joint effects of NLR and PLR on functional outcomes of acute ischemic stroke (AIS). Methods: Our study involved 448 eligible patients with first-ever AIS. Clinical and laboratory data were collected on admission. Unfavorable functional outcome was defined as a modified Rankin Scale score of 3-6 at 3 months after AIS. Cox proportional hazard model and spline regression models was used to estimate the effect of NLR and PLR on risk of adverse outcomes after the last patient who completed a three-month follow-up was enrolled. Results: After adjusting confounders, NLR were significantly associated with the unfavorable functional outcomes (P-trend<0.001). So were PLR (P-trend<0.001). NLR was discovered to have higher predictive value than PLR (AUC=0.776, 95%CI = 0.727–0.825, P<0.001; AUC=0.697, 95%CI=0.641-0.753, P<0.001). The optimal cutoff values for NLR and PLR was 3.51 and 141.52, respectively. Stratified analysis performed by cox proportional hazard model showed that high level of NLR and PLR (NLR≥3.51, PLR≥141.52) presented the highest risk of unfavorable functional outcomes (adjusted HR, 3.77; 95% CI: 2.38-5.95; P<0.001). Followed by single high level of NLR (adjusted HR, 2.32; 95% CI: 1.10-4.87; P=0.027). Single high level of PLR (NLR<3.51, PLR≥141.52) also showed higher risk than low level of the combination, but it did not reach statistical significance (adjusted HR, 1.42; 95% CI: 0.75-2.70; P=0.285). No obvious additive [relative excess risk due to interaction (RERI) not significant] or multiplicative (adjusted HR, 0.71; 95%CI: 0.46-1.09; P=0.114) interaction was found between the effects of NLR and PLR on the risk of unfavorable functional outcomes. Conclusion: This study demonstrated that both NLR and PLR were independent predictors of 3-month functional outcomes of AIS. They may help to identify high-risk patients more forcefully when combined together.